Soil suitability estimation for housing purposes in landslide-prone areas. The case of Karya village, Patras, W. Greece - Koukis, G.; Sabatakakis, N.; Lainas, S. (Bulletin of the Geological Society of Greece, 2007)
This paper discusses a method of soil suitability estimation for housing purposes in landslide-prone areas based on engineering geological criteria. The studied places, Karya and Neo Souli villages are located on the eastern part of the city of Patras. Several instability problems were identified triggered by heavy rainfalls, especially during extreme meteorological events. The soil formations were classified in several geotechnical units while typical geotechnical profiles and slip sections were drawn. Limit equilibrium slope stability analyses were established in order to investigate the critical slide conditions, using shear strength parameters estimated from laboratory and in-situ testing. The studied area was finally divided into five zones according to the suitability of the encountered ground regarding housing purposes